PERAN ORANG TUA DAN DUKUNGAN SOSIAL TERHADAP KEMAMPUAN MEMBACA SISWA (STUDI KASUS SDN PEBATAN 01) - Nila Sabrina, Dinda; Tri Setiyoko, Didik; Saefudin Wahid, Farhan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Reading ability is a fundamental skill that playsa crucial role in supporting students’ academic success at the elementary school level. However, in reality, there are still many students who experience difficulties in reading, both in terms of fluency and comprehension. This issue is also found among Fourth-grade students at SDN Pebatan 01, where some students still read haltingly despite having participated in literacy acruvutues at school. This condition is presumed to be related to the less optimal role of parents in assisting children’s learning at home and the limited social support from the surrounding environment. This study aims to describe the role of parets and the forms of social support in improving students’ reading abilities. The research employs a qualitative approach using a case study method. Data were collected through observation, interviews, and documentation involving teachers, prents, and students. Data analysis was carried out through the stages of data reduction, data display, and conclusion dawing. The results indicate that parental involment in assisting children’s reading activities is still not optimal, mainly due to time constraints and a lack of awareness regarding the importance of literacy. In aadtion, social support from the school environment and the community has not fully contributed to improvingstudents’ reading skills. The literacy programs implemented by the school havenot yet produced evenly distributed outcomes among students. Therefore, improving studets’ reading ability requires collaboration among schools, parents, and the social eniroment.